Epidermodysplasia verruciformis - symptoms, causes, diagnosis and treatment - Sutejo, Richard (PT. Kalbe Farma Tbk., 2014)
Epidermodysplasia verruciformis is a rare dermal disease made popular by â€œTree Manâ€ in November 2007. The disease is caused by rare autosomal recessive hereditary genetic disorder located on chromosome 17 which causes mutation on EVER1 and EVER2 genes. An abnormality in Major Histocompatibility Complex Class II (MHC II) allele DC-DQ has also been documented in patients in America, Europe and Africa continents. These mutations increased vulnerabilities to Human Papillomavirus (HPV) causing uncontrolled wart growth, prominent in arms, neck, and legs. The common initial detection of Epidermodysplasia verruciformis is through biopsy on predicted premalignant and malignant skin lesions. Further confirmatory analysis can be performed by in-situ hybridization and polymerase chain reaction. The medical treatment is generally not definitive; typically with topical drugs such ad imiquimod, 5-fluorouracil, vitamin A derivative 13-cis retinoic acid, interferon alpha or cholecalciferol analogues (Vitamin D). For severe cases, surgical procedures to remove excessive warts are necessary.Epidermodysplasia verruciformis merupakan penyakit kulit langka yang dikenal sejak kemunculan manusia pohon pada November 2007. Penyakit ini disebabkan oleh kelainan genetik keturunan autosomal resesif di kromosom 17 yang menyebabkan mutasi gen EVER1 dan EVER2. Selain itu, juga ditemukan kelainan pada Major Histocompatibility Complex kelas II(MHC II) pada alel DC-DQ pada pasien di benua Amerika, Eropa dan Afrika. Semua mutasi abnormal ini menyebabkan kerentanan terhadap infeksi Human Papillomavirus (HPV) yang menyebabkan pertumbuhan kutil tak terkontrol terutama di daerah tangan, leher dan kaki. Tindakan awal deteksi Epidermodysplasia verruciformis adalah biopsi daerah lesi yang diprediksi premaligna dan maligna, dapat dikonfirmasi dengan proses in-situ hybridization dan polymerase chain reaction. Terapi tidak definitif, dermatologis biasanya menggunakan obat topikal seperti imiquimod and 5-fluorourasil, senyawa turunan vitamin A asam 13-cis retinoik, interferon alfa atau analog kolekalsiferol (Vitamin D). Untuk kasus parah, diperlukan operasi untuk membuang kutil yang berlebih.Â